Dual economies, Kaldorian underemployment and the big push - Giovanni Valensisi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2008)
This paper develops a two-sector model with specific factors of production à la Ricardo-Viner-Jones, in which agriculture is subject to diminishing returns and market-clearing wages, while increasing returns and efficiency wage mechanisms prevail in industry. The asymmetric interaction of the two sectors, jointly with the dualistic structure of the labor market, is such that the model may display multiple equilibra and a low-development trap under plausible parametrization. Additionally, parametric increases of sectoral TFP may reduce the basin of attraction of the low-equilibrium and increase the steady state level of capital stock (and wages) for the stable equilibrium of complete industrialization.
Keywords: 330; Dualökonomie; Produktivität; Entwicklung; Industrialisierung; Theorie der Arbeitslosigkeit; Mehr-Sektoren-Modell; Entwicklungstheorie